Continuous antibiotic prophylaxis in the setting of prenatal hydronephrosis and vesicoureteral reflux - Wong, Nathan C. (Can Urol Assoc J, 2017)
Continuous antibiotic prophylaxis (CAP) has traditionally been offered for children with recurrent urinary tract infections (UTIs) or those at risk, including children diagnosed with prenatal hydronephrosis (HN) and vesicoureteral reflux (VUR). However, indications for antibiotic prophylaxis are controversial, data on who should benefit from this therapy is conflicting and, thus, guidelines are unable to provide conclusive recommendations. In the setting of prenatal HN, although randomized trials are currently underway, most evidence is derived from low- to moderate-quality observational studies. Although there is no benefit in those with low-grade HN, a systematic review of the available studies showed that high-grade HN patients on prophylaxis experienced fewer infections with an estimated number needed to treat of 7. On the other hand, there are eight randomized trials that have investigated the use of antibiotic prophylaxis in the setting of VUR. Although four of the studies have demonstrated some value of prophylaxis and the other four have not, meta-analysis has shown an overall benefit of antibiotic prophylaxis in preventing infections. The observed differences are likely due to different inclusion criteria and study heterogeneity. Although generalizing results of meta-analyses to all children is tempting, an individualized approach, by determining which patients best behave like those of the included studies, is recommended.